Etiological and pathomorphological investigations in calves with coronaviral pneumoenteritis - Ismet Kalkanov (Macedonian Veterinary Review, 2019)
The aim of the present study was to report the primary gross and microscopic lesions, as well as etiological agents of field cases of pneumoenteritis in neonate and juvenile calves. The research was done with 370 calves from 6 cattle farms in 4 regions of the country. The age of the animals was from 24 hours to 25 days. Clinical and epidemiological studies were carried out with newborn and growing calves in all farms. For rapid antigenic and viral detection of pathogens, Rainbow calf scour 5 BIO K 306 Detection of Rota, Corona, E.coli F5, Cryptoand Clostridium perf. in bovine stool (BIOX Diagnostics, Belgium), and Monoclonal Antibody anti-bovine Coronavirus FITC conjugated) 0,5 ml (20X), BIO 023, (BIOX Diagnostics, Belgium) were used. Eighteen carcasses of calves with signs of pneumoenteritis syndrome (PES) were submitted to gross anatomy and histopathological studies. Bovine coronavirus (BCoV) was the main etiological agent involved in calf pneumoenteritis. The macro- and micro lesions in the lung and the ileum of calves affected by PES are relevant with regard to the differential diagnosis of the syndrome and its differentiation from respiratory (IBR, BVD, BRSV, M. haemolytica etc.) and intestinal (Cryptosporidium parvum, bovine rotaviruses, bovine coronaviruses and Escherichia coli K99 (F5) diseases in this category of animals.